Legislative, institutional and policy reforms to combat violence against women in Afghanistan: Policy reforms to combat violence against women in Afghanistan - Qazi Zada, Sebghatullah (The Indian journal of international law, 2021)
Since the fall of Taliban regime in 2001, the government of Afghanistan, in a bid to promote human rights and specifically women’s rights, made several legislative and institutional advances. These included the establishment of the Afghanistan Independent Human Rights Commission (AIHRC) as a national human rights institution, Ministry of Women’s Affairs, Departments of Women’s Affairs and Gender, Human Rights Units in various ministries and the passing of the Law on Elimination of Violence against Women (EVAW Law) through a Presidential Decree in 2009. Afghanistan is a signatory to several international human rights instruments, including the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). International treaties and Conventions to which Afghanistan is a signatory forbid all types of discrimination against girls and women and oblige Afghanistan to eliminate all types of discrimination, violence and other possible detrimental practices against women. This paper aims to critically analyse the international obligations of Afghanistan concerning violence against women and the necessary legal and institutional amendments for providing better protection for such victims. This paper has pursued a reformist agenda to eliminate violence against women, which is largely caused by weaknesses in Afghanistan’s legal, institutional and policy frameworks regarding women. The existing legal environment in Afghanistan comprises three incoherent sources of law—State legal code, customary practices and Islamic sharia law. Adopting and implementing the recommendations are likely to contribute significantly to the emancipation of women in Afghanistan. Thus, as part of the reformist agenda adopted by this paper, violence against women warrants urgent legal, institutional and policy reforms.